2022
DOI: 10.3390/jpm12060931
|View full text |Cite
|
Sign up to set email alerts
|

Who to Be Treated: Nomogram Using Self-Reported Periodontal Screening Instrument among English-Speaking Adults in Multi-Ethnic Singapore

Abstract: Periodontal disease is a major public health problem. This study aimed to develop a nomogram using a self-reported periodontitis screening instrument in predicting severe periodontitis (SP), defined by the World Workshop on Classification of Periodontal and Peri-Implant Diseases and Conditions, and evaluate its utility in clinical setting. An Akaike information criterion selected multivariable model was developed to predict SP using a self-reported questionnaire, with a nomogram developed based on its regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…These same factors also hold relevance when considering "Any Periodontitis". Our results align with a previously published study 15 , affirming the suitability of the 8-item questionnaire for identifying individuals with periodontitis.…”
Section: Any Periodontitissupporting
confidence: 92%
See 3 more Smart Citations
“…These same factors also hold relevance when considering "Any Periodontitis". Our results align with a previously published study 15 , affirming the suitability of the 8-item questionnaire for identifying individuals with periodontitis.…”
Section: Any Periodontitissupporting
confidence: 92%
“…While most studies concerning self-reported periodontitis involve the validation of questionnaires 22,23 , our study introduces a tool with clinical utility and applicability. Notably, such a tool has only been previously published in the context of an Asian population of older persons 15 .…”
Section: Any Periodontitismentioning
confidence: 99%
See 2 more Smart Citations